The extraction method for the separation of lithium isotopes using B12C4/B15C5/B18C6-ionic liquid systems. (3rd January 2023) - Zhou, Xiaolong; Zhang, Pengrui; Meng, Qingfen; Mao, Lianjing; Ju, Huiqun; Shao, Fei; Jing, Yan; Jia, Yongzhong; Wang, Shuxuan; Zou, Xingwu; Sun, Jinhe
Abstract : B12C4 systems achieve better 6 Li enrichment in the organic phase and B15C5 systems achieve better 7 Li enrichment in the aqueous phase. Abstract : Lithium isotopes play an essential role in the nuclear industry. The extraction method with crown ethers as extractants is considered as one of the promising methods for lithium isotope separation with good application prospects. However, the effects of crown ethers with different cavity sizes in the system containing ionic liquids on isotope enrichment in organic solution/aqueous solution have not been systematically investigated. With three typical benzo crown ethers (B12C4, B15C5 and B18C6) as extractants and the mixtures of ionic liquids and anisole as solvents, the effect of crown ethers on the extraction rate of Li +, separation factor and δ 7 Li variation in organic solution/aqueous solution was investigated with varied solvent composition, lithium salts and concentration of crown ethers. The order of extraction rates was: B15C5 (40.88%) > B18C6 (38.12%) > B12C4 (23.35%) and the order of isotope separation factors was: B15C5 (1.024) > B12C4 (1.023) > B18C6 (1.010) under optimized conditions. The δ 7 Li in aqueous solution of B15C5 systems was higher than those corresponding to the B12C4 and B18C6 system while the δ 7 Li in the organic solution of the B12C4 systems was more negative than those corresponding to the B15C5 and B18C6 system. So, B12C4 systems achieve better 6 Li enrichment in the organic phase and B15C5 systems achieve better 7 Li enrichment in the aqueous phase.